Insights Into the Template Effect on Nanostructured CuO Catalysts for Electrochemical CO2 Reduction to CO - Ye, Xiaodong; Jiang, Yangyang; Chen, Xi; Guo, Benshuai; Mao, Songbai; Guo, Yafei; Zhao, Chuanwen (Frontiers in Energy Research, 2022)
Electrochemical CO2 reduction to CO using copper-based catalysts has been recognized a promising approach to realizing anthropologic carbon cycle. However, copper-based catalysts face the challenges of low reduction activity and poor selectivity in CO2 reduction reaction. Tuning particle size and oxygen vacancy represents an efficient strategy for boosting their activity and selectivity. Herein, we reported the preparation of nanostructured CuO catalysts for selective electrochemical CO2 reduction to CO. Several templates were employed in the template-assisted hydrothermal process to regulate the particle size and oxygen vacancy. Structure-property-activity relationships of the CuO nanostructures depend on the template effect. CuO-PVP and CuO-SDS synthesized using polyvinylpyrrolidone (PVP) and sodium dodecyl sulfate (SDS) as templates exhibited smaller particles sizes and higher concentrations of oxygen vacancy defects. Under the applied potential of −0.93 V vs. RHE, the desired CuO-PVP and CuO-SDS catalysts exhibited good CO2 reduction activity with high electrochemical surface area normalized partial current density of 2.21 and 1.37 mA/cm2 for CO production and outstanding CO selectivity with high faradaic efficiencies of 48.2 and 50.5%. Density functional theory (DFT) calculations indicated that oxygen vacancies in the CuO nanostructures not only promoted CO2 adsorption and activation but facilitated CO desorption from the catalyst surface, and therefore boosted the activity and CO selectivity in CO2 reduction. The results have deepened the understanding of the structure-property-activity relationships of CuO catalysts, and these will provide guidance for designing highly efficient and robust catalysts for electrochemical CO2 reduction to CO.